RENEWAL OF CONTROL OF INTERNAL LAND RIGHTS CONSTI-TUTIONAL LAW PERSPECTIVE - Irwansyah Irwansyah; Herlina Hanum Harahap; Muhammad Ansori Lubis (Jurnal Ilmiah METADATA, 2026)
Article 33 paragraph (3) of the 1945 Constitution mandates the state that everything related to land as part of the earth, water and natural resources contained therein in Indonesia must and must be managed and utilized for the greatest prosperity of the Indonesian people. The state's right to control land is regulated in Article 1 and Article 2 of the UUPA, which also states that land controlled by the state is an elaboration of the state's right to control land, water and space. State land as land directly controlled by the state is land that is not attached to any land rights, as regulated in the UUPA. Control of land rights from a juridical-theoretical perspective is control based on rights, which are protected by law and generally give authority to the rights holder to physically control the land that is being claimed, for example the land owner uses or takes advantage of the land that is being claimed, not handed over to another person